Evaluasi Implementasi Blended Learning pada Mata Kuliah Fisika Modern dengan Model Diskrepansi - Napsawati, Napsawati; Syamsudduha, St.; Rasyid, Muhammad Nur Akbar; Agussalim, Agussalim (Universitas Nurul Huda, 2024)
The purpose of this paper is to describe the essence that occurs at each stage in the discrepancy evaluation model which consists of the Design, Installation, Process and Product stages related to the Blended Learning method in the modern spectacles course at the Muslim University of Maros. Based on the type of research used, this research is included in program evaluation research using the discrepancy evaluation model. The research sample consisted of 14 people plus 1 modern physics lecturer. Data collection was carried out using a mixed method with data collection instruments using, (1) interview guidelines, (2) questionnaires with a Likert scale model and (3) documentation. The data analysis technique used for qualitative data is data analysis using the Miles and Huberman model. This data analysis technique consists of data collection, data reduction and drawing conclusions. As for the quantitative data, the data analysis technique used is quantitative descriptive analysis and the calculation of the coefficient of determination. The results showed that (1) there was no discrepancy in the design stage (2) there was a discrepancy in the installation stage of 0.04 (3) there was a discrepancy in the Process stage of 0.23 (4) there was a discrepancy in the Product stage of 0. 78. So that the Blended Learning lectures can be continued with suggestions for improvement, namely (1) Lecturers continue to carry out their obligations to carry out face-to-face lectures, (2) Require students to study material in Google Classroom, (3) Uploaded material has various forms.